The gods of ancient Greece: identities and transformations - Bremmer, Jan N.; Erskine, Andrew (Edinburgh Leventis studies, 2010)
The Greek gods are still very much present in modern consciousness. Although Apollo and Dionysos, Artemis and Aphrodite, Zeus and Hermes are household names, it is much less clear what these divinities meant and stood for in ancient Greece. In fact, they have been very much neglected in modern scholarship. This book brings together a team of international scholars with the aim of remedying this situation and generating new approaches to the nature and development of the Greek gods in the period from Homer until Late Antiquity. The book looks at individual gods, but also asks to what extent cul